PAA/ZnO Raspberry-Shaped Composite Microspheres Decorated with Ag Nanoparticles as Cleanable SERS Substrates - Wu, Jun Yi (ACS Omega, 2020)
[Image: see text] A PAA/ZnO/Ag heterostructure composite material was prepared by a reduction method. The properties of composite particles are analyzed by transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), UV–visible spectroscopy, and Raman spectroscopy. Ag nanoparticles play an important role in PAA/ZnO/Ag composite microspheres, conferring new SERS properties and functions to PAA/ZnO/Ag. The intensity of the SERS signal of PAA/ZnO/Ag irradiated with UV light decreased from 10 000 to below 500. The SERS detection limit of R6G obtained was reduced to 1 × 10(–6) M. The PAA/ZnO/Ag composite particles show a very good degradation effect on R6G under UV light irradiation. This study has developed a new synthesis method to prepare SERS signal enhancement materials with self-cleaning effects. According to the experimental results, the PAA/ZnO/Ag composite material has higher sensitivity than the PAA/ZnO composite material.